(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
The study aimed to analyze and test the role of Information Systems effectiveness in crisis management across its three stages (pre-crisis, during-crisis, and post-crisis) at the Directorate of Agriculture and Agrarian Reform in Latakia Governorate. The study adopted the descriptive-analytical approach and employed Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) to test the hypotheses and verify the quality of the structural model. Data were collected through a questionnaire distributed to a purposive sample of 200 employees occupying administrative and technical positions related to information systems and crisis management within the Directorate. The findings revealed a low level of availability of Information Systems effectiveness and crisis management practices in the studied environment. However, the structural analysis results demonstrated a positive and statistically significant effect of Information Systems effectiveness on crisis management across its three stages, with high explanatory power for the proposed model. The results also showed that the strongest effect was found in the pre-crisis stage, followed by the during-crisis stage, while the effect was relatively lower in the post-crisis stage. These findings highlight the importance of improving Information Systems effectiveness in enhancing organizational preparedness, response, and recovery within public sector institutions.